Hierarchical rupture growth evidenced by the initial seismic waveforms - Takashi Okuda (Nature Portfolio, 2018)
The degree to which small and large earthquakes share the same rupture processes remains unknown. Here, the authors reveal earthquakes of magnitude 3–5 share almost identical growth processes shared, but while they are controlled by some characteristic structures, their final size remains unpredictable.